Risk Factors of Persistent Diarrhoea in Children below Five Years of Age - Roy Smrity; Bazlul Karim ASM; Kumar Das Shiplu; Ibne Maksud Shams; Nasreen Sultana Shahjadi; Sultana Azmeri (Journal of Pediatric Health And Nutrition, 2019)
Background Persistent diarrhoea is a commonly observed phenomenon both in Bangladesh and all over the developing countries. It is the single most important cause of diarrhoea related deaths in the community, accounting for over half of them. If associated factors are properly identified & treated, it is possible to prevent most cases of persistent diarrhoea. Objective This study was undertaken to find out the possible risk factors associated with persistent diarrhoea in children below 5 years of age. Methods This was a prospective analytical case control study carried out in a tertiary care hospital, Dhaka. A total of 30 consecutive cases of persistent diarrhoea and 60 consecutive acute diarrhoea controls (matched for age and sex) under 5 comprised the study subjects in this study. Children beyond the age and whose parents didn’t give written consent were excluded from the study. Data were collected using a structured questionnaire and a standered case definition of acute & persistent diarrhoeawere adopted. Data were later processed and analyzed using SPSS (Statistical Package for Social Science version 12) in the year 2012. Results were considered statistically significant when p value was <0.05. Results According to the study, 56.6% of cases and 63.3% of controls were in the ‘6 to 12 months’ age group and about two-third of the participants in both cases 20 (66.7%) and controls 39 (65.0%) were males.Strong association was found with ‘bottle feeding’ RR=2.2556; 95% CI: 1.259, ‘presence of blood/mucus’ RR=2.5038; 95% CI: 1.4129, ‘WAZ≤ 2)’ RR=2.8867; 95% CI: 1.7202 and ‘early complementary feeding [RR=4.67; 95% CI: 2.5017-8.7175 and OR=7.8858; 95% CI: 3.6791-16.9 Conclusion In the present studyfour factors showed some association with persistent diarrhoea, namely: ‘use of animal milk’; ‘antibiotic use during acute diarrhoea’; ‘history of diarrhoea in previous 3 months’ and ‘pre-lacteal feed’. Strong association was found with ‘bottle feeding practices’ ‘presence of blood &/or mucus in stool’, WAZ <-2 and ‘early complementary feeding
Keywords: acute diarrhea